Rational design, supramolecular synthesis and solid state characterization of two bicomponent solid forms of mebendazole - Gutiérrez, Eduardo Luciano (2020)
Two novel bicomponent solid forms of mebendazole (MBZ) were developed as a means to modulate its psychochemical and pharmaceutical properties. Supramolecular synthesis of MBZ A or C with perchloric or methyl sulfuric acids yields two salts of 1 : 1 stoichiometry, which were analyzed through single crystal X-ray diffraction. MBZ perchlorate crystallizes in the P21/n space group, while MBZ methyl sulfate crystallizes in the P1 space group. The API and its counterions are interconnected in both crystal packings by an R22(8) supramolecular motif. The 3-dimensional crystal structure is also stabilized by other strong intermolecular hydrogen bonds as well as non-classical interactions. FT-IR spectra are consistent with the inclusion of the anions in the crystal structure. MBZ perchlorate is stable up to 210 °C when it undergoes endothermic loss of the ester moiety. MBZ methyl sulfate is stable up to 160 °C when endothermic elimination of the methylcarbamate moiety occurs. The solubility behavior of MBZ perchlorate, studied by UV-visible spectroscopy, suggests an improvement by a factor of seven with respect to MBZ A, in the apparent solubility of MBZ in 0.1 mol L-1 HCl. Further experiments are required to evaluate both the stability of the solids and the maximum solubility of the API.